Study of variations of sagittal diameter of lumbar vertebral canal in population of Rajasthan, India - Bhaumik, Meghna; Bhaumik, Uday (International Journal of Research in Medical Sciences, 2017)
Background:The lumbar part of vertebral canal houses the cauda equina and narrowing of the bony ring of the canal, which may be developmental or acquired may lead to compression of these nerve roots and causes low back-pain. The increasing number of low back pain due to sedentary life style and other associated factors had provide a large number of radiographs, CT-scan, MRI Scans of lumbar spine. The present study was conducted in the western region of Rajasthan state to measure the sagittal diameter of lumbar canal in relation to distinguish difference in the variation in dimensions of both sexes. Aim is to evaluate the sexual differences in sagittal diameter of the lumbar vertebral canal. Methods: Lateral view radiographs of 1000 patients (756 males and 289 females) between the age group of 20-60 years, with the history of low back pain reporting to the various outpatient departments of Neurosurgery, Orthopedics of S.M.S hospitals, Jaipur formed the material for the present study. Results: There is a steady increase in sagittal diameter of lumbar spinal canal from L1 to L5 vertebrae. The dimensions of sagittal diameter of lumbar spinal canal in male population were higher than female population. Conclusions: A steady increase is noted in antero-posterior diameter of canal in all lumbar vertebrae. The minimum values of antero-posterior diameter of canal is 17.68 mm for vertebra L1 and the maximum value is 21.98 mm at vertebra L5 in males. In females, the minimum value of antero–posterior diameter is 17.48 mm at L1 vertebra and the maximum value is population with male values are higher than the female values and showing highly significant changes at L1 vertebra.